ANALISIS MISKONSEPSI PESERTA DIDIK PADA MATERI SISTEM PERNAPASAN MANUSIA - Nana Pramawati Dewi; Martini Martini; Aris Rudi Purnomo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
The purpose of this research was to analyze student misconception and describe the factors that cause students misconceptions about human respiratory system materials. This research was descriptive research that involved 65 students in VIII grades from two classes in SMPN 1 Sidoarjo. The instruments that used in this research was four-tier test completed with certainty of response index (CRI) and interview. The results showed there was student misconceptions on human respiratory system materials that consist of structure concept and function of the human respiratory organs, respiratory mechanisms, respiratory frequency, respiratory volume and diseases human respiratory system. The percentage of students’s results of the Respiratory System material was 62,15% students have a misconception. The factors that caused students misconceptions include the students themselves, learning method, teaching method, and daily context.